(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
يهدف هذا البحث إلى دراسة مسألة الاهتزازات النظامية لمجموعة من السوائل اللزجة الشعرية في أنبوب. أثبتنا نتائج تصف طبيعة طيف المسألة المدروسة في حالة أنبوب دوّار وأنّ جملة العناصر الجذرية ( العناصر الخاصة والعناصر المرتبطة ) تشكل قاعدة آبل – ليدسكي. استخدمنا بعض النتائج من نظرية المؤثرات مترافقة ذاتياً في دراسة طبيعة طيف المسألة المدروسة في حالة أنبوب ثابت. Our aim of this paper is studying the problem on normal oscillations of system of capillary viscous fluids in vessel. We prove results about the spectrum of the problem for rotating vessel and prove that the systems of root elements ( eigenelements and associated elements ) form an Abel-Lidsky basis. Also , we use some results from the theory of J-self adjoint operators in studying the spectrum of the problem for non-rotating vessel.